Pola-Pola Isi Pemberitaan Media Online mengenai Pemberian Izin Usaha Pertambangan untuk Muhammadiyah dan Nahdlatul Ulama - Romadlan, Said; Maududi, Mukhlish Muhammad; Wahdiyati, Dini; Putra, Gilang Kumari; Yunan, Zulfahmi Yasir (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2025)
The Government's granting of Special Mining Business Permits for religious community organizations has sparked agreeing and disagreeing attitudes from various circles. Those who agree with this Government policy can equalize the welfare of the people and be fair. Meanwhile, those who disagree consider this policy only for the benefit of the government on the one hand, and can plunge religious organizations themselves. The controversy regarding the acceptance of mine management by religious organizations can also be seen in the patterns of online media reporting. This study focuses on the patterns of online media reporting on the acceptance of mine management by Muhammadiyah and Nahdlatul Ulama (NU). The research method uses quantitative content analysis with categories of news patterns including the number of news reports, the determination of sources, and the tendency of content. The results of the study show that the patterns of online media coverage on the issue of granting mining business licenses for Muhammadiyah and NU from the number of news reports are relatively large, which shows that this issue is important. The dominant sources are from Muhammadiyah and NU figures, while the tendency of the content is neutral, although there is not much disagreement with the agreement. Here, online media has a dual function, namely as a social integration influenced by media routines, and as a social control determined by the natural function of media ideology.